Why are some countries richer than others? : a reassessment of Mankiw-Romer-Weil's test of the neoclassical growth model - Felipe, Jesus; McCombie, J. S. L.; Asian Development Bank (ERD working paper, ISSN 1655-5252, 2002)
Abstract (s. vii).
Keywords: taloudelliset mallit : Aasia; taloudellinen kehitys : Aasia